Louisiana Clinical Data Research Network: establishing an infrastructure for efficient conduct of clinical research. (12th May 2014) - Khurshid, Anjum; Nauman, Elizabeth; Carton, Tom; Horswell, Ron
Abstract: The state of Louisiana, like the nation as a whole, is facing the salient challenge of improving population health and efficiency of healthcare delivery. Research to inform innovations in healthcare will best enhance this effort if it is timely, efficient, and patient-centered. The Louisiana Clinical Data Research Network (LACDRN) will increase the capacity to conduct robust comparative effectiveness research by building a health information technology infrastructure that provides access to comprehensive clinical data for more than 1 million patients statewide. To ensure that network-based research best serves its end-users, the project will actively engage patients and providers as key informants and decision-makers in the implementation of LACDRN. The network's patient-centered research agenda will prioritize patients' and clinicians' needs and aim to support evidence-based decisions on the healthcare they receive and provide, to optimize patient outcomes and quality of life.